Butterfly-shaped keloid as a rare case of Wolf’s isotopic response - Chhikara, Pragati; Jakasaniya, Jaykumar; Patel, Kashyap (Indian Journal of Case Reports, 2025)
Wolf’s isotopic response is defined as the appearance of a new dermatosis at the site of a previously healed, unrelated skin disorder. We describe a rare case of a 64-year-old immune-competent female who developed a butterfly-shaped keloid at the site of an insect bite 3 years prior. This case highlights the unusual presentation of keloids as a result of insect bite, emphasizing the importance of early diagnosis and treatment. Treatment with intralesional triamcinolone acetonide injections began, with plans for ongoing monitoring to prevent recurrence. This report contributes to a better understanding of keloid pathogenesis by emphasizing the importance of taking into account atypical triggers and the psychosocial impact such lesions have on patients.